Adolescents’ Legal Socialization: Effects of Interrogation and Miranda Knowledge on Legitimacy, Cynicism, and Procedural Justice - Vidal, Sarah (Youth violence and juvenile justice, 2017)
This study examined how detained youths’ (N = 98) actual experiences with the law, including frequency of contact with the police and knowledge about the Miranda warning and interrogation practices, relate to their perceptions of support, fairness, and trust toward the police. Results show that more police contacts were associated with lower perceived obligation to obey the law and higher cynicism toward the law and also moderated the relationships between age and police legitimacy and race/ethnicity and police legitimacy and procedural justice. Comprehension of the Miranda warning was associated with lower perceived obligation to obey the law and procedural justice, and knowledge about police interrogation practices was associated with lower perceived police legitimacy. These findings suggest the potential of legal socialization as a mechanism for intervention among offending adolescents; programs that promote positive youth-police interactions may help minimize negative attitudes and foster perceptions of trust and fairness toward the police.